EFFECTIVENESS OF DRYING COAL POWDER IN OBTAINING ECO-QUALITY BRIQUETTES (American Journal of Technology and Applied Sciences, 2023)
In the process of obtaining the coal briquettes from the coal dust were analyzed the methods of maximum moisture loss in its composition. This was aimed at reducing the amount of toxic gases released during the combustion of briquettes for consumption.